2015
DOI: 10.1038/cr.2015.152
|View full text |Cite
|
Sign up to set email alerts
|

NudC regulates actin dynamics and ciliogenesis by stabilizing cofilin 1

Abstract: Emerging data indicate that actin dynamics is associated with ciliogenesis. However, the underlying mechanism remains unclear. Here we find that nuclear distribution gene C (NudC), an Hsp90 co-chaperone, is required for actin organization and dynamics. Depletion of NudC promotes cilia elongation and increases the percentage of ciliated cells. Further results show that NudC binds to and stabilizes cofilin 1, a key regulator of actin dynamics. Knockdown of cofilin 1 also facilitates ciliogenesis. Moreover, deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 52 publications
6
50
0
Order By: Relevance
“…These results are consistent with the function of NudC in mammalian cells (Zhou et al, 2003;Aumais et al, 2003). Depletion of NudC in zebrafish by morpholinos exhibited several ciliary defects, such as body curvature, pericardial edema, hydrocephalus, and defective left-right asymmetry, which are similar to that of Cas9/NudC-gRNA-treated embryos (Zhang et al, 2015). Furthermore, the cilia in NudC morphants were abnormally elongated, orientated in random directions, and beat in an uncoordinated manner.…”
Section: Physiological Significance Of Nudc Familysupporting
confidence: 76%
See 3 more Smart Citations
“…These results are consistent with the function of NudC in mammalian cells (Zhou et al, 2003;Aumais et al, 2003). Depletion of NudC in zebrafish by morpholinos exhibited several ciliary defects, such as body curvature, pericardial edema, hydrocephalus, and defective left-right asymmetry, which are similar to that of Cas9/NudC-gRNA-treated embryos (Zhang et al, 2015). Furthermore, the cilia in NudC morphants were abnormally elongated, orientated in random directions, and beat in an uncoordinated manner.…”
Section: Physiological Significance Of Nudc Familysupporting
confidence: 76%
“…Further results show that NudC colocalizes with cofilin 1 especially at the leading edge, and influences the stability of cofilin 1 via an Hsp90-independent pathway. Knockdown of NudC promotes cilia elongation and increases the percentage of ciliated cells, which is similar to those by actin cytoskeleton disruption or cofilin 1 depletion (Zhang et al, 2015). Exogenous expression of cofilin 1 significantly suppresses the defective ciliogenesis induced by NudC depletion, but not vice versa.…”
Section: Cellular Functions Of Nudc Family Nudcsupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, WIPI1, WIPI2 and WIPI4 share NudC606162 as a novel partner protein. Moreover, we found that WIPI4 directly associates with ATG2 (refs 40, 43, 71, 72, 73) (via N15/D17) and that this complex also contains AMPK and ULK1 in fed conditions.…”
Section: Discussionmentioning
confidence: 99%